(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Overview of the role of traditional medicine in supporting cancer treatment in Vietnam. Methods: A scoping review searched for articles published on the data of the Ministry of Science and Technology within 10 years in Vietnam related to the research objective, according to the criteria PRISMA-ScR standard. Results: Out of 57 articles found on the database, 10 articles were filtered out that met the selection criteria. All included articles were in vitro studies (cell models), evaluated the inhibitory and cytotoxic effects of extracts from some traditional Vietnamese medicine on cancer cell lines. The cancer cell lines included in 10 studies were liver cancer (5), lung cancer (5), breast cancer (3), cervical cancer (3), leukemia (2), epithelial cancer (2), pancreatic cancer (1), ovarian cancer (1) and stomach cancer (1). Conclusion: Research on traditional medicine in cancer treatment in Vietnam in the past 10 years has mainly been in vitro research, there has not been much experimental or clinical research.